KOSAKATA BATU DALAM BAHASA-BAHASA DAERAH DI INDONESIA: ANALISIS LINGUISTIK BANDINGAN HISTORIS - Rijal, Syamsul (Fakultas Ilmu Budaya, Universitas Mulawarman, 2015)
The phenomenon of gemstone or in Indonesia known as “batu akik” happened greatly in the early to the middle of 2015 and has become attention among the people in Indonesia. Although it cannot be identified precisely when the phenomenon of people massively wearing and collecting gemstones has begun, this study aims to present an early review of this phenomenon seeing from linguistics study. This study revealed three linguistics points regarding to this phenomenon. First, from several vocabulary of “batu”, most of them have the same phonetic form, that is [batu]. Second, the variation of “batu” vocabulary experienced changes in bilabial sound from /b/ to become /w/; extra aspirated voice [Bh] in phoneme [b]; and bilabial phoneme /b/ becomes dorsa velar /k/. Third, this study reveals that people’s interest in wearing and collecting gemstone all over Indonesia happened as the result of cultural similarity which lies in vocabulary “batu” that exists almost in all tribes, regions, and cities in Indonesia.Keywords: gemstone, local language, linguistic comparison